Wealth effects on consumption: evidence from the euro area - Ricardo M. Sousa (European Central Bank (ECB), 2009)
This paper estimates the wealth effects on consumption in the euro area as a whole. I show that: (i) financial wealth effects are relatively large and statistically significant; (ii) housing wealth effects are virtually nil and not significant; (iii) consumption growth exhibits strong persistence and responds sluggishly to shocks; and (iv) the immediate response of consumption to wealth is substantially different from the longrun wealth effects. By disaggregating financial wealth into its major components, the estimates suggest that wealth effects are particularly large for currency and deposits, and shares and mutual funds. In addition, consumption seems to be very responsive to financial liabilities and mortgage loans.
Keywords: E21; E44; D12; 330; Consumption; financial wealth; housing wealth; Vermögenseffekt; Immobilienpreis; Börsenkurs; Konsumentenverhalten; Eurozone